2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1615820
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectropulse Intracellular Perturbation and Electropermeabilization Technology: Phospholipid Translocation, Calcium Bursts, Chromatin Rearrangement, Cardiomyocyte Activation, and Tumor Cell Sensitivity

Abstract: Nanosecond, megavolt-per-meter pulsed electric fields scramble the asymmetric arrangement of phospholipids in the plasma membrane, release intracellular calcium, trigger cardiomyocyte activity, and induce apoptosis in mammalian cancer cells, without the permeabilizing effects associated with longer, lower-field pulses. Dose dependencies with respect to pulse width, amplitude, and repetition rate, and total pulse count are observed for all of these phenomena. Sensitivities vary among cell types; cells of lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…A single nanosecond pulse causes depolarization, calcium waves, and contraction of cardiomyocyte fibers [6]. Adrenal chromaffin cells also respond to a single pulse as short as 3 ns with elevated intracellular calcium levels and catecholamine release.…”
Section: Microfluidic Channels Separated By Pulse-gated Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…A single nanosecond pulse causes depolarization, calcium waves, and contraction of cardiomyocyte fibers [6]. Adrenal chromaffin cells also respond to a single pulse as short as 3 ns with elevated intracellular calcium levels and catecholamine release.…”
Section: Microfluidic Channels Separated By Pulse-gated Membranesmentioning
confidence: 99%
“…Nanosecond, megavolt-per-meter pulsed electric fields nondestructively perturb the intracellular environment, causing calcium bursts [1,2], eosinophil sparklers [3], vacuole permeabilization [4], nuclear chromatin rearrangement [5], activation of excitable cells (cardiac myocytes and adrenal chromaffin cells) [6], and the appearance of apoptotic indicators such as release of cytochrome c into the cytoplasm [7], loss of mitochondrial membrane potential, and caspase activation [8,9]. Nanoelectropulse-induced killing of cancer cells and shrinking of tumors has been demonstrated in vitro and in vivo [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that nanoelectropulses (ns MV/m electric fields) induce apoptosis in malignant cells without damaging the external cell membrane [1][2][3]. Molecular dynamics simulations indicate that subnanosecond 5-20 MV/m pulses could minimize nanoporation of the cell membrane, and allow intracellular electro-manipulation to dominate over membrane effects [2].…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] These effects have, among other things, generated interest in the electromanipulation of intracellular structures for inducing apoptosis and understanding gene transfection mechanisms.…”
Section: Introductionmentioning
confidence: 99%